Topology optimization of bimorph piezoelectric energy harvesters considering variable electrode location. (19th July 2019) - de Almeida, Breno V; Cunha, Daniel C; Pavanello, Renato
Abstract: With the advances on additive manufacturing techniques for piezoelectric materials, it is becoming steadily more viable to produce piezoelectric structures with complex geometries. Since such devices can have more sophisticated shapes, the application of topology optimization techniques can be used to explore optimized topologies for piezoelectric energy harvesters with varying thickness. In this context, challenges arise in the application of the electrode equipotential constraints during the optimization process. In this work, an algebraic formulation was proposed to tackle this issue when optimizing a harvester's topology. A bimorph piezoelectric energy harvester with series connection of the piezoceramic layers was modeled under plane strain hypothesis in the thickness profile, first not applying and then considering periodicity constraints in the optimization process, while concurrently improving the electrodes. This paper shows how the open-circuit harvesting device was modeled and its finite element formulation. Lastly, an adaptation of the bidirectional evolutionary structural optimization method is proposed, in order to approach this problem.